TINGKAT PEMAHAMAN TENAGA TEKNIS KEFARMASIAN TERHADAP OBAT PATEN DAN OBAT GENERIK DI KOTA PADANG - Verawaty, Verawaty; Dewi, Irene Puspa; Kota, Fanny Millenia (Jurnal Riset Kefarmasian Indonesia, 2022)
Patent drugs are drugs that still have patent rights and can only be produced by the manufacturer of the patent holder. while generic drugs are drugs whose patents have expired, so that they can be produced by all pharmaceutical companies. The purpose of this study was to determine the level of understanding of the pharmaceutical technical staff of Padang City on patent drugs and generic drugs. This research is a descriptive observational study using data collection instruments in the form of online questionnaires (google forms). The research variable is the respondent's level of understanding of generic and patent drugs. The respondents of this study were Pharmacy Technical Staff of Padang City, aged 20 years, both male and female, as many as 55 respondents. The sampling technique in this study was non-purposive sampling in accordance with the inclusion and exclusion criteria. Determination of the sample size in this study using the Slovin formula with an error rate of 5%. Collecting data by distributing online questionnaires via Google Forms. The data obtained is coded and entered into an Excel worksheet. The results showed that the level of understanding of the pharmaceutical technical staff of Padang City on patent drugs and generic drugs was categorized as sufficient (74.5%).